Analysis of electricity consumption and thermal storage of domestic electric water heating systems to utilize excess PV generation. (15th November 2021) - Yildiz, Baran; Bilbao, Jose I.; Roberts, Mike; Heslop, Simon; Dore, Jonathon; Bruce, Anna; MacGill, Iain; Egan, Renate J.; Sproul, Alistair B.
Abstract: Water heating is one of the most energy intensive applications in households and domestic electric water heating systems (DEWH) offer large thermal storage for moving electrical load across the day. This study uses a unique dataset from 410 households and presents a comprehensive analysis of electricity consumption and hot water draw of DEWH for the Australian context. Using the real-world data and thermal energy modelling tool TRNSYS, the study analyses the potential of storing and using excess PV generation in DEWH and investigates the impact of different daily hot water draw profiles, PV and DEWH size on the potential for excess PV utilization. The results show that households on average use 6 kWh of energy for DEWH and 142 L of hot water daily. Potential excess PV utilization is highly dependent on the household's daily hot water draw profile and is also affected by seasonality. On average, excess PV generation from a 4.5 kW PV system can provide 48% of daily DEWH energy for a household with a typical working family profile, which corresponds to a 28% increase in PV self-consumption. Highlights: Typical daily hot water draw profiles are presented for Australian households. Typical daily electricity profiles of domestic water heating systems are presented. On average households use 142L of hot water per day results in 6 kWh of electricity. Excess generation from 4.5 kW PV system provides 48% of daily water heating energy. PV self-consumption is improved by 28% via utilizing excess PV for water heating.